The English Camps as Method of Promoting Fun English at Elementary School Level in Indonesia - Rachmawati, Meida; Widjajanti, Suzana; Ahmad, Ahmad; Aslan, Aslan (Tapis: Jurnal Penelitian Ilmiah, 2020)
This article aimed to promote English in elementary school students through a fun learning method, called the Fun English Camp. Several studies had been conducted to encounter the best solution to handle this issue. The researchers used PRISMA Protocol as an instrument to collect the data that has been widely used in the process of selecting relevant articles. The researchers reviewed twenty five scientific publications, related to Fun English Camp that has become an English learning approach for beginner students. Through a review of twenty five scientific publications, for instance book and journal, the researchers got scientific evidence that introduction of a learning method with the term Fun English camp has an impact on promoting language learning for elementary school children in Indonesia. Thus, the fun English camp method can be an interesting method to be applied by elementary school curriculum design in Indonesia. Keywords: English Camps, Learning Method, Fun English Learning